PERLINDUNGAN HUKUM BAGI NASABAH PERBANKAN BERDASARKAN STANDAR LAYANAN DI PT.BANK NEGARA INDONESIA (PERSERO) TBK: Asiana Granadia Dyah Buwana - admin, admin; Hariz Hamdallah, Muhammad Andika (Reformasi Hukum, 2018)
transactions at banks. The customer as the main actor in banking transactions has the right to be served well without any difference or discrimination from one customer to another. If one customer is not satisfied with the service of one of the Bank's officers namely the Security Guard, the customer has the right to submit his complaint to the Head of the Bank. The purpose of this study was to determine the legal protection of BNI customers based on banking service standards and to find out the standard BNI service procedures for customers in accordance with the Banking Act. This study uses a normative juridical approach. Conclusions: 1. PT Bank Negara Indonesia (Persero) Tbk has protected its customers by issuing Company Guidelines for resolving customer complaints, and banking service standards. This can be seen from the availability of Company Guidelines in order and detail in each flow of the process of handling and settling customer complaints which are then equipped with SOP (Standard Service Procedure) for each BNI officer, namely the service standards for Security Guard, Teller and CSO officers and Outlet Leaders. 2. Rules regarding Customer Service Standards at PT Bank Negara Indonesia (Persero) Tbk, are in accordance with: a) Law of the Republic of Indonesia Number 8 concerning Consumer Protection.